Identification of Common Genes Refers to Colorectal Carcinogenesis with Paired Cancer and Noncancer Samples. (30th January 2018) - Zhang, Lihua; Yang, Yonglong; Cheng, Lin; Cheng, Yu; Zhou, Hong-Hao; Tan, Zhi-Rong
Abstract : Colorectal cancer is a malignant tumor which harmed human beings' health. The aim of this study was to explore common biomarkers associated with colorectal carcinogenesis in paired cancer and noncancer samples. At first, fifty-nine pairs of colorectal cancer and noncancer samples from three gene expression datasets were collected and analyzed. Then, 181 upregulation and 282 downregulation common differential expression genes (DEGs) were found. Next, functional annotation was performed in the DAVID database with the DEGs. Finally, real-time polymerase chain reaction (PCR) assay was conducted to verify the analyses in sixteen colorectal cancer and individual-matched adjacent mucosa samples. Real-time PCR showed that MCM2, RNASEH2A, and TOP2A were upregulated in colorectal cancer compared with adjacent mucosa samples ( MCM2, P < 0.001 ; RNASEH2A, P < 0.001 ; TOP2A, P = 0.001 ). These suggested that 463 DEGs might contribute to colorectal carcinogenesis.